2020
DOI: 10.26434/chemrxiv.12235181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Potential Drug Targets and Prediction of the Potential Impact of High Risk Non Synonymous Single Nucleotide Polymorphism in SARS-CoV-2 3C like Proteinase (3CLpro): A Computational Approach

Abstract: On January 2020, a new coronavirus (officially named SARS-CoV-2) was associated with alarming outbreak of a pneumonia-like illness, which was later named by the WHO as COVID-19, originating from Wuhan City, China. Although many clinical studies involving antiviral and immunomodulatory drug treatments for SARS-CoV-2 all without reported results, no approved drugs have been found to effectively inhibit the virus so far. Full genome sequencing of the virus was done, and uploaded to be freely available for the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…It forms a strong hydrogen bond of length 1.91 Å with Asp187 and also forms hydrophobic interactions with Tyr54, Met49, Met165, Phe140, Leu141, Cys145 and Leu27 and polar interactions with His41, Gln189, His 164, His163, His172, Asn142, Ser144 and Thr26. It has been reported that binding to the Arg188/Gln189 site reduces the catalytic activity of the protein [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It forms a strong hydrogen bond of length 1.91 Å with Asp187 and also forms hydrophobic interactions with Tyr54, Met49, Met165, Phe140, Leu141, Cys145 and Leu27 and polar interactions with His41, Gln189, His 164, His163, His172, Asn142, Ser144 and Thr26. It has been reported that binding to the Arg188/Gln189 site reduces the catalytic activity of the protein [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 contains the results of the ADMET studies performed on the ten compounds. Of the ten finalized compounds, seven of them had excellent intestinal absorption, an important requirement for a drug since the intestine serves as the primary site of absorption of a drug that is taken orally [ 61 ]. The water solubility of the compounds was quite low, but there are means to increase the solubility of a drug in water such as particle size reduction, nanosuspension and the use of surfactants [ 63 ].…”
Section: Resultsmentioning
confidence: 99%